EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN MODEL DISCOVERY LEARNING SERTA MODEL THINK PAIR SHARE MATERI KUBUS DAN BALOK DITINJAU DARI KATEGORI KECERDASAN EMOSIONAL PADA KEMAMPUAN BERPIKIR MATEMATIS TINGKAT TINGGI PESERTA DIDIK SMP - Yudi Pramono Pawiro; Budiyono Budiyono; Isnandar Slamet (Journal of Mathematics and Mathematics Education, 2015)
Abstract: The objective of this research was to know the effect of the learning models on the high order mathematical thinking skill viewed from the emotional quotient of the students. The learning models compared were model of the PBL, model of the DL and model of the TPS. This research used the quasi experimental research. It’s population was all of the students in Grade VIII of State Junior Secondary Schools in Sukoharjo. The samples of the research were taken by using the stratified cluster random sampling technique and consisted of 253 students. They were grouped into three classes, namely: 87 in Experimental Class 1, 84 in Experimental Class 2, and 83 in Experimental Class 3. The instruments to gather the data were test of high order mathematical thinking skill on the learning topic of cube and beam, and emotional quotient questionnaire. The proposed hypotheses of the research were analyzed by using the two way analysis of variance with unbalanced cells. The results of the research were as follows. 1) Model of the PBL results in a better high order mathematical thinking skill than model of the DL, and  model of the TPS. Model of the DL results same high order mathematical thinking skill  with TPS. 2) Emotional quotient gives students a different effect on high order mathematical thinking skill on the learning topic of cube and beam. The students with the high emotional quotient have a better high order mathematical thinking skill than those with the moderate emotional quotient and those with the low emotional quotient, the students with the moderate emotional quotient have a better  high order mathematical thinking skill than those with the low emotional quotient. 3) There was no interaction the aforementioned learning models and the categories of the emotional quotient on the high order mathematical thinking skill of the students.Keywords: PBL, DL, TPS, High Order Mathematical Thinking Skill and Emotional Quotient.